2015
DOI: 10.1080/13691058.2015.1104386
|View full text |Cite
|
Sign up to set email alerts
|

Financial obligations and economic barriers to antiretroviral therapy experienced by HIV-positive women who participated in a job-creation programme in northern Uganda

Abstract: Economic costs are commonly cited as barriers to women’s use of antiretroviral therapy (ART) in sub-Saharan Africa; however, little is known about how changes in women’s income influence economic barriers to care. We analysed in-depth interviews with 17 HIV positive women who participated in a job-creation programme in northern Uganda and two key informant interviews with programme staff to examine lingering economic barriers to care experienced after programme enrolment. We found that participants continued t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…However, if more and more people encounter informal charges at facilities that are actually designated to provide free services, the poor will stay away from seeking health services due to lack of money. A number of studies have shown that when health facilities impose charges outside formal policy guidelines, important health system goals such as access, quality and financial risk protection can be undermined [9] , [39] , [42] , [43] . A two-tier health system can emerge which provides good quality care for those with money and poor quality for patients who cannot afford to pay [12] .…”
Section: Discussionmentioning
confidence: 99%
“…However, if more and more people encounter informal charges at facilities that are actually designated to provide free services, the poor will stay away from seeking health services due to lack of money. A number of studies have shown that when health facilities impose charges outside formal policy guidelines, important health system goals such as access, quality and financial risk protection can be undermined [9] , [39] , [42] , [43] . A two-tier health system can emerge which provides good quality care for those with money and poor quality for patients who cannot afford to pay [12] .…”
Section: Discussionmentioning
confidence: 99%